Phytochemical contents and antioxidant properties of polyherbal effervescent tablets formulated with different effervescent agents - Mohd Sukri, Nurul Syafuhah; Muhammad, Norhayati; Abdul Rahim, Nur Fazira (2022)
The production of effervescent tablets by using effervescent agents in pharmaceutical products has increased due to the convenient way of swallowing the tablets. The aim of this study was to formulate polyherbal extract of Phyllanthus niruri, Strobilanthes crispus and Orthosiphon aristatus in effervescent tablets using different agents as well as to evaluate the phytochemical contents and antioxidant properties of those formulated tablets. Eight different types of formulated tablets were prepared with different effervescent agents. Total phenolic content (TPC), total flavonoid content (TFC), 2,2-diphenyl-1- picrylhydrazyl (DPPH) radical scavenging activity and ferric-reducing antioxidant power (FRAP) assays were used to evaluate the antioxidant properties of the formulated tablets. The effervescent tablet formulated with 20% acidic agent especially with citric acid (T1) displayed significant properties (p < 0.05) on phytochemical contents (TPC: 36.76 ± 0.50 mg GAE/g DW; TFC: 55.54 ± 3.60 mg RE/g DW) and antioxidant activities (DPPH: IC50: 61.60 ± 0.31 mg/mL; FRAP: 57.05 ± 0.98 mg Fe2+/g DW). In conclusion, the high content of acidic agents resulted in high phytochemical contents and antioxidant activities among the formulated polyherbal effervescent tablets. The application of effervescent agents in formulating polyherbal extract into fast-disintegrating tablets could offer opportunities in producing nutraceutical and oral drugs.